Structural and Functional Changes of the Heart in Young Adult Tennis Players - Hsu-Chun Huang; Wei-Ting Lin; Ruei-Shyang Liu; I-Wei Lu; Chia-Chin Chiang; Hsiang-Chun Lee (Journal of Physiological Investigation)
This cross-sectional observational study investigated undetermined cardiac remodeling and functional adaptation in young tennis players. Fourteen males with regular tennis training (at least three times a week, mean playing age 8.3 ± 3.8 years, tennis group, tennis) and 12 males without any racket sports engagement (the control group, [CTL]) underwent comprehensive cardiac measurements using real-time three-dimensional echocardiography, recording of baseline characteristics, blood tests, and estimation of VO2 max by 12-min running. Data were analyzed to compare the two groups. Two groups were of similar age (mean age, CTL 20.9 ± 2.4 vs. tennis 22.5 ± 4.4 years, P = 0.235) and with similar body size. Compared with the CTL, Tennis group had slower pulse rate (70.9 ± 7.0/min vs. CTL 85.5 ± 9.6/min, P < 0.001), greater VO2 max (43.4 ± 3.8 mL/Kg/min vs. CTL 33.1 ± 4.8 mL/Kg/min, P < 0.001), but similar blood levels of hematocrit, NT-pro-brain natriuretic peptide, and creatinine phosphokinase. The tennis group had greater left ventricle posterior wall thickness (0.90 ± 0.06 cm vs. CTL 0.81 ± 0.10 cm, P < 0.001), greater right ventricle (RV) volume index (77.8 ± 9.6 mL vs. CTL 64.9 ± 10.1 mL, P = 0.003), and greater left atrial volume index (26.9 ± 5.5 mL/m2 vs. CTL 21.9 ± 2.7 mL/m2, P = 0.006). The tennis group had significantly increased RV strain (free wall strain, −26.5 ± 3.7% vs. CTL −23.3 ±2.8%, P = 0.025). However, the global longitudinal strains in the left atrium and left ventricle were similar between the two groups. Cardiac remodeling in young tennis players includes right ventricular dilatation with enhanced dynamic function, an enlarged left atrium with well-preserved function, and a predominant posterior wall thickening of the left ventricle.